Prospects for the implementation of artificial intelligence in renewable energy management - A. T. Rostova; A. A. Sokolov; G. V. Masyutina (Современная наука и инновации)
The article is an attempt at research in the field of the use of artificial intelligence (AI). The efficiency of using artificial intelligence (AI) technologies to control the load at the plant, energy generation from renewable energy sources, and the use of AI in these processes is analyzed. The research of the current state and prospects of AI development in various industries and directions, the complexity in the multidimensional use of Artificial Intelligence at power plants in the areas of "green energy" are analyzed.